2017
DOI: 10.3390/su9081435
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable Supply Chain Management Implementation–Enablers and Barriers in the Textile Industry

Abstract: Abstract:The distinct definition of accordance in the perceived barriers and enablers for sustainable supply chain management (SSCM) policy implementation has been the subject of various research studies, but a distinct focus on the textile sector has been the object of limited previous attention. However, it has been found that it affects the approach to developments in company approaches to sustainable supply chain management within that industry. This article presents the results of an in-depth comparative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
88
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(108 citation statements)
references
References 56 publications
(87 reference statements)
4
88
0
1
Order By: Relevance
“…To this end, this paper pointed out that managers need to work through and manage SSCM tensions to successfully implement SSCM. In particular, supplier-related issues can be resolved by developing trust-based, collaborative relationships (Brix-Asala et al, 2018;Oelze, 2017), as well as regular contact and feedback that could reduce monitoring requirements and risks on the part of suppliers (Hajmohammad & Vachon, 2016;Xiao et al, 2019).…”
Section: Managerial Implicationsmentioning
confidence: 99%
“…To this end, this paper pointed out that managers need to work through and manage SSCM tensions to successfully implement SSCM. In particular, supplier-related issues can be resolved by developing trust-based, collaborative relationships (Brix-Asala et al, 2018;Oelze, 2017), as well as regular contact and feedback that could reduce monitoring requirements and risks on the part of suppliers (Hajmohammad & Vachon, 2016;Xiao et al, 2019).…”
Section: Managerial Implicationsmentioning
confidence: 99%
“…Oelze [33] studied the existence of consensuses in the perception of barriers and enablers of sustainable supply chain implementation in the textile industry. The author conducted a case study with 23 interviews across 10 textile companies and showed that collaboration can enable sustainable policy implementation and reduce barriers.…”
Section: Sustainability Issues In Textile and Apparel Supply Chainsmentioning
confidence: 99%
“…This new, modern type of SCI often involves both internal (e.g., intraorganizational integration) and external (e.g., customer and supplier integration) dimensions [5], whereby firms can concentrate on their specialized areas and complete other functions through strategic alliance and cooperation with diverse partners along the supply chain. Such SCI goes beyond organizational boundaries, thus enabling firms to effectively avoid making costly (and probably risky) investments, particularly those highly asset-specific and customized ones because not all critical activities and services need to be carried out independently in-house [8][9][10].…”
Section: Sci and Innovation With Ecological Concerns: Resource Dependmentioning
confidence: 99%